Recent trends in public policy formulation: A bibliographic approach - Murillo Zamora, Carlos (2024)
The article presents a state-of-the-art analysis, not exhaustive, based on a review of literature on public policies and their interpretation. This is contextualized within the changes brought about by globalization, the transformations of state agencies, and the growth of non-state actors in the international system. The study also delves into wicked problems, which are on the rise, and the crises of the present century. Additionally, it explores the significance of the design and co-design of policies, a crucial aspect for understanding the subject of study. The purpose is to provide an account of constructs and their variables, identify main approaches and trends in policy design, and offer bibliography as a reference for those interested in this field. While not a comprehensive review, it encompasses a wide range of texts. The work is part of a research project on recent trends in the design and co-design of policies. As a result, it enumerates concepts rather than reaching conclusions or making statements. In this sense, it serves as a consultation document for specific or general policy analyses. It is a preview of a research project on “Public policy design in complex contexts: the case of Costa Rica”, assigned to the School of Public Administration, University of Costa Rica.